The Relationship between Enterprise Risk Management and Cost of Capital - Muhammad Kashif Shad; Fong-Woon Lai; Amjad Shamim; Michael McShane; Sheikh Muhammad Zahid (Asian Academy of Management Journal, 2022)
This paper investigates the effect of enterprise risk management (ERM) implementation on the cost of capital (cost of debt [Cd], cost of equity [Ce], and weighted average cost of capital [WACC]) for the oil and gas industry. The research is conducted using panel data analysis from 2008?2017 for 41 oil and gas companies publicly listed on the Bursa Malaysia. ERM implementation data is collected from company annual reports, while the cost of capital data is obtained from Thomson Reuters DataStream. The results indicate that an increase in the level of ERM implementation reduces the cost of capital, which we argue is one mechanism through which ERM increases firm value. Future research can use our investigation to delve deeper into ERM and value creation topics.